Alopecia Areata Incognita and Diffuse Alopecia Areata: Clinical, Trichoscopic, Histopathological, and Therapeutic Features of a 5-Year Study - Aurora Alessandrini; Michela Starace; Francesca Bruni; Nicolò Brandi; Carlotta Baraldi; Cosimo Misciali; Pier Alessandro Fanti; Bianca Maria Piraccini (Mattioli1885, 2019)
Background: Alopecia areata is a nonscarring hair loss that usually causes round patches of baldness, but alopecia areata incognita (AAI) and diffuse alopecia areata (DAA) can cause a diffuse and acute pattern of hair loss. Objective: To analyze the clinical, trichoscopic, histological, and therapeutic features of AAI and DAA. Methods: The study was designed to include data of patients with histological diagnosis of AAI and DAA enrolled in our Hair Disease Outpatient Consultations. Results: DAA had a greater involvement of the parietal and anterior-temporal regions, while AAI manifested itself mainly in the occipital-parietal regions. The most frequent pattern was empty yellow dots, yellow dots with vellus hairs, and small hair in regrowth, but the presence of pigtail hair was found almost exclusively in those with AAI. In cases of DDA, the finding of dystrophic hair and black dots was more frequent. The most frequent trichoscopic sign in both diseases was the presence of empty yellow dots, which, however, were described in a higher percentage in cases of DAA. The diseases have a benign course and are responsive to topical steroid therapy. Conclusions: Trichoscopy is very important for the differential diagnosis between the 2 diseases and to select the best site for biopsy. In the presence of diffuse hair thinning, these entities must be considered.